BEHAVIOR OF EXCLUSIVE BREASTFEEDING AND ASSOCIATED FACTOR AMONG MOTHERS IN THE FORMAL SECTOR, INDONESIA - Devi Angeliana Kusumaningtiar; Nur Wahidah (Universitas Airlangga, 2023)
Introduction: Based on data from the Strategic Plan (Strategic Plan of the Ministry of Health) in 2018 nationally, coverage of infants obtained exclusive breastfeeding in 2018 which is 68.74%. Based on data on the coverage of exclusive breastfeeding at Puskesmas Kelurahan Utara, 45.5% is still below the Indonesian government's national target. Aims: Determine the factors related to exclusive breastfeeding behavior in Posyandu RW 06 Puskesmas Kelurahan Utara Kembangan Utara West Jakarta. Methods: This study uses a quantitative research type with a cross-sectional design. The study population was all mothers who had babies aged 7 to 12 months with a sample size of 94 mothers with stratified sampling as the sampling technique.. Data analysis was performed using the chi-square test. Result: Univariate results were the highest proportion of mothers who gave exclusive breastfeeding (66%), good knowledge (72.3%), working mothers (51.1%) and supporting families (55, 3%). There is a relationship between maternal knowledge (PR = 2,308, 95% CI: 1,362-3,909), and family support (PR = 5,365, 95% CI: 2,437-11,811) with exclusive breastfeeding behavior in Posyandu Puskesmas Kelurahan Kembangan Utara West Jakarta. Conclusion: Mothers give exclusive breastfeeding because it is easy to give without the hassle of making formula milk and the cost is cheap so that mothers can save on expenses without having to buy milk formula and baby's weight always increases every month. It is hoped that you can add material and provide education about the role of the family in breastfeeding exclusively when the mother controls the womb with the family.